Media education competitions: An efficient strategy for digital literacies? - Pereira, Luís (2017)
In this paper we present results from research in Portugal about competitions in schools that involve digital education (2010-2015). The aim of this study is to discuss its effectiveness as a strategy for developing Media Education. The 16 activities we have collected are mostly targeted at the school population and show an emphasis on media production, a dimension that is often not considered part of formal learning, which is more focused on reading than on writing. The results lead us to raise questions about the importance of non-formal education. Interestingly, most of these initiatives have been designed to take place in the school context and are, in various ways, supported by the Ministry of Education, a situation which blurs the boundaries between formal and non-formal learning. The analysis of the data leads us to this specific recommendation: these initiatives should be formally evaluated in order to understand their real impact on the acquisition of news media education skills.